PENGARUH PENGAWASAN LURAH TERHADAP KINERJA STAFF DALAM PENGELOLAAN PROGRAM PEREKAMAN E-KTP DI KELURAHAN MARGAJAYA KECAMATAN BOGOR BARAT KOTA BOGOR - Ilham Solihin; Nandang S. Zenju; Denny Hernawan (LPPM Universitas Djuanda Bogor, 2015)
The purpose of this study is; 1) To determine the performance of the implementation of the e-ID card recording program in the Village of Margajaya District of West Bogor; 2) To determine the supervision by the headman of the village staff performance the Village of Margajaya District of West Bogor; 3) To determine the effect on the performance of staff supervision headman in e-KTP Recording Program in the Village of Margajaya District of West Bogor.The method used in this research is descriptive method of analysis, which is the method of analysis is descriptive research that aims to explain certain social phenomena. The population in this study were all employees of the Village Margajaya District of West Bogor as many as 15 people. In this study, the sampling technique used was simple random technique. The number of samples in this study amounted to 14 employees at the Village Margajaya District of West Bogor. Analysis of the data against two variables in this study is the Product Moment Correlation Coefficient.The results showed that the analysis of surveillance headman, obtained an average value of 3.86 which, according to the criteria of interpretation of the figures were high criteria. While the analysis of the performance of pegwai, obtained an average value of 3.92 which, according to the criteria of interpretation of the figures were high criteria. There headman influence on the performance of staff supervision in the management of e-ID card recording programs in Sub Margajaya District of West Bogor based on the analysis turned out to be very significant where the result is greater than tcount > ttable (5.599 > 2.178). Keywords: performance, monitoring headman, e-ID Card